(untitled) (Strathmore Law Journal, 2016)
When Kenya’s President, Uhuru Kenyatta, opened the first ever World Trade Organisation (WTO) Ministerial Conference to be held on African soil, he knew that the Doha Development Agenda (DDA)1 ceremoniously agreed upon in 2001, and of which his country had been an ardent promoter, would be put under the guillotine. So much was made abundantly clear by Michael Froman, the United States of America Trade Representative (USTR), in an op-ed published in the Financial Times just two days prior to the Conference. Froman argued that "Doha was designed in a different era, for a different era, and much has changed since", and that "it is time for the world to free itself of the strictures of Doha’, before concluding presciently that ‘Nairobi will mark the end of an era". The Conference of 2015 closed with a Ministerial Declaration and the ‘Nairobi Package’ comprising a series of six Ministerial Decisions on agriculture, cotton and issues related to least developed countries (LDCs). WTO’s Director-General, Roberto Azevêdo, concluded with optimism that, similar to two years ago in Bali, the WTO had once again delivered ‘major, multilaterally-negotiated outcomes’ at Nairobi. All these things will be analyzed in the following lines.